Fungsi Manajemen Strategi Dalam Peningkatan Status Akreditasi Rumah Sakit: Studi Teoritis - Giska Dianvayani; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Strategic management has a very important role and needs to be implemented in improving the accreditation status of the hospital. The strategy that has been made must be implemented properly in order to ensure development and sustainability. This strategy must be applicable to all hospital parties in order to improve service quality and accreditation status. The purpose of writing this scientific article is to find out and review from a theoretical point of view various literatures. The method used is a theoretical study by analyzing and comparing existing theories. The results of this theoretical study are the function of strategic management in improving accreditation status by carrying out procedures so that it can assist hospitals in making better plans with a more logical, rational and systematic approach for each option that will be found by forming a plan. It can be concluded that in improving the quality of health, strategic management is also needed to improve services. With accreditation strategic management, the hospital becomes the object of focus or a process of assessing and determining the eligibility of the hospital according to service standards set by an independent accreditation agency. So that it can improve the image and trust of patients in choosing health care facilities. For hospitals strategic management is very important and needs to be done optimally to support the improvement of accreditation status. So agencies improve infrastructure facilities, adequate human resources and supporting facilities.